Forever young - Dylan, Bob, 1941- (Atheneum Books for Young Readers, 2008)
Bob Dylan's classic 1974 anthem Forever Young is reimagined by award-willing illustrator Rogers. In this picture book, the lyrics follow the story of a young boy who travels through Dylan's life, living in the footsteps of a musical legend.